2021
DOI: 10.2147/tacg.s317721
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Profile of the Dystrophin Gene Reveals New Mutations in Colombian Patients Affected with Muscular Dystrophinopathy

Abstract: Background Duchenne and Becker muscular dystrophies (DMD/BMD) are the most common human dystrophinopathies with recessive X-linked inheritance. Dystrophin gene deletions and duplications are the most common mutations, followed by point mutations. The aim of this study is to characterize the mutational profile of the dystrophin gene in Colombian patients with DMD/BMD. Material and Methods Mutational profiling was determined in 69 affected patients using Sanger sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…The present study detected a prevalence of nonsense variants of 24.5%, which is slightly higher. The percentage of nonsense variants in our population was also significantly higher when compared to other South American countries, where the presence of nonsense singlenucleotide variants varied from 11.6 to 16.7% [5,18,23]. A single-center study conducted in Mexico, however, found similar results regarding the prevalence of nonsense pathogenic variants (n = 11/49; 22.45%) [24].…”
Section: Discussionsupporting
confidence: 63%
“…The present study detected a prevalence of nonsense variants of 24.5%, which is slightly higher. The percentage of nonsense variants in our population was also significantly higher when compared to other South American countries, where the presence of nonsense singlenucleotide variants varied from 11.6 to 16.7% [5,18,23]. A single-center study conducted in Mexico, however, found similar results regarding the prevalence of nonsense pathogenic variants (n = 11/49; 22.45%) [24].…”
Section: Discussionsupporting
confidence: 63%
“…BMD has a lower incidence rate than DMD, but due to longer life expectancy, is not much less prevalent. Better access to massive parallel sequencing has increased the diagnosis of BMD in ethnic groups beyond high-income countries [8][9][10][11][12] and has also improved the diagnosis of BMD through prenatal [13] and neonatal screening programs [14,15].…”
Section: Improved Diagnostics For Becker Muscular Dystrophymentioning
confidence: 99%